High-voltage insulator ceramic and method for producing the same

CN122977825APending Publication Date: 2026-10-27GUANGZHOU POWER SUPPLY BUREAU GUANGDONG POWER GRID CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611024579.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,高压绝缘子陶瓷的陶瓷烧结温度高,晶界度低、缺陷多,易引发局部电场集中,绝缘稳定性差;同时,绝缘子陶瓷的抗弯强度低、易脆性断裂,服役寿命短

Benefits of technology

[0040]本申请的制备方法通过采用绝缘子陶瓷基体原料、第一烧结助剂、第二烧结助剂和粘结剂的混合原料,利用片状氢氧化镁的热处理产物作为第一烧结助剂,该片状氢氧化镁的热处理产物处于高能亚稳态,表面具有丰富的悬挂键和晶格松弛区域,对绝缘子陶瓷基体原料中的SiO2、Al2O3及第二烧结助剂中的钾钡液相的化学亲和力极高,在烧结过程中,能更早(约低50-100℃)形成连续低粘度液相,显著降低烧结温度、拓宽烧结窗口,同时在特定方向上形成液相分布抑制晶粒粗化、促进刚玉结晶度提升、优化显微结构,进而改善介损、耐污闪与力学韧性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977825A_ABST
    Figure CN122977825A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of insulators, in particular to a high-voltage insulator ceramic and a preparation method thereof. The preparation method comprises the following steps: mixing an insulator ceramic matrix raw material, a first sintering aid, a second sintering aid and a binder, then performing pressure moulding, and then performing sectional temperature rising sintering treatment to obtain the high-voltage insulator ceramic; the first sintering aid comprises a heat treatment product of flaky magnesium hydroxide; the preparation method of the heat treatment product of flaky magnesium hydroxide comprises the following steps: heating flaky magnesium hydroxide at 700 DEG C-850 DEG C for 1h-2h; and the second sintering aid comprises one or more of talcum powder, barium carbonate, potassium carbonate, barium oxide and potassium oxide. The high-voltage insulator ceramic has excellent electrical insulation performance and mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of insulator technology, and in particular to high-voltage insulator ceramics and their preparation methods. Background Technology

[0002] With the rapid development of power systems, high-voltage transmission lines, as the core equipment for power transmission, are of paramount importance in terms of safety and reliability. Among them, high-voltage insulator ceramics are the core insulation components of high-voltage transmission lines, and they need to withstand the effects of high voltage, high current, and harsh environments.

[0003] In traditional methods, high-voltage insulator ceramics are prepared by mixing, molding, and high-temperature sintering using kaolin, feldspar, quartz, and alumina powder as the main raw materials. However, high-voltage insulator ceramics have high sintering temperatures, low grain boundary density, and many defects, which easily lead to local electric field concentration and poor insulation stability. At the same time, insulator ceramics have low bending strength, are prone to brittle fracture, and have a short service life.

[0004] Therefore, there is an urgent need to prepare high-voltage insulator ceramics with excellent electrical insulation properties and mechanical strength to ensure the stability of power grid operation. Summary of the Invention

[0005] Based on this, one or more embodiments of this application provide high-voltage insulator ceramics and methods for preparing the same. These high-voltage insulator ceramics possess excellent electrical insulation properties and mechanical strength.

[0006] One aspect of this application provides a method for preparing high-voltage insulator ceramics, comprising the following steps:

[0007] The insulator ceramic matrix raw material, the first sintering aid, the second sintering aid and the binder are mixed to obtain a mixture;

[0008] The mixture is pressed into shape to obtain a raw blank;

[0009] The green blank is sintered to obtain the high-voltage insulator ceramic;

[0010] The first sintering aid includes a heat-treated product of flake magnesium hydroxide; the preparation method of the heat-treated product of flake magnesium hydroxide includes the following steps: heating flake magnesium oxide at 700℃-850℃ for 1h-2h;

[0011] The second sintering aid includes one or more of talc, barium carbonate, potassium carbonate, barium oxide, and potassium oxide.

[0012] In some embodiments, the thickness of the flake magnesium hydroxide is 0.1 μm-0.2 μm, and the aspect ratio is (2-10):1; and / or,

[0013] The thickness of the heat-treated flake magnesium hydroxide is 0.1 μm-0.2 μm, and the aspect ratio is (2-10):1.

[0014] In some embodiments, the ceramic matrix material for insulators includes quartz and alumina; and / or,

[0015] The adhesive includes one or more of polyvinyl alcohol and polyvinyl butyral.

[0016] In some embodiments, the insulator ceramic matrix raw material, by weight, comprises 60-65 parts of quartz and 37-47 parts of alumina; and / or,

[0017] The alumina is alumina powder; the particle size D50 of the alumina powder is 200nm-400nm.

[0018] In some embodiments, the mass ratio of the insulator ceramic matrix raw material to the first sintering aid is 100:(1-4); and / or,

[0019] The mass ratio of the insulator ceramic matrix raw material to the second sintering aid is 100:(7-9); and / or,

[0020] The mass ratio of the insulator ceramic matrix raw material to the binder is 100:(0.5-0.8).

[0021] In some embodiments, the step of mixing the insulator ceramic matrix raw material, the first sintering aid, the second sintering aid, and the binder includes:

[0022] The insulator ceramic matrix raw material and the first sintering aid are mixed and ball-milled to obtain the first mixture; the ball milling conditions include: the ball milling speed is 100rpm-200rpm and the ball milling time is 6h-8h.

[0023] Mix the first mixture, the second sintering aid, and the binder; and / or,

[0024] The step of molding the mixture includes: loading the mixture into a mold and pressing it at 10MPa~15MPa.

[0025] In some embodiments, the conditions for ball milling further include: ball milling using mixed grinding balls;

[0026] The mixed grinding balls include a first grinding ball, a second grinding ball, and a third grinding ball with a mass ratio of 1:(0.8-1.2):(0.8-1.2);

[0027] The first grinding ball has a particle size of 4.5mm-5.5mm;

[0028] The particle size of the second grinding ball is 7.5mm-8.5mm;

[0029] The particle size of the third grinding ball is 9.5mm-10.5mm.

[0030] In some embodiments, the sintering process includes:

[0031] The temperature was increased from 20℃-40℃ to 650℃-750℃ at a rate of 4.5℃ / min-5.5℃ / min.

[0032] The temperature was increased from 650℃-750℃ to 1275℃-1325℃ at a rate of 2.5℃ / min-3.5℃ / min.

[0033] Keep warm at 1275℃-1325℃ for 25-35 minutes;

[0034] The temperature was reduced from 1275℃-1325℃ to 1225℃-1250℃ at a rate of 0.5℃ / min-1.5℃ / min.

[0035] Keep warm at 1225℃-1250℃ for 2-3 hours.

[0036] One or more embodiments of this application also provide high-voltage insulator ceramics, which are prepared using the preparation method described above.

[0037] In some embodiments, the high-voltage insulator ceramic has one or more of the following characteristics:

[0038] (1) Breakdown strength ≥ 10 kV / mm;

[0039] (2) Bending strength ≥ 100 MPa.

[0040] The preparation method of this application uses a mixture of insulator ceramic matrix raw materials, a first sintering aid, a second sintering aid, and a binder. The heat-treated product of flake magnesium hydroxide is used as the first sintering aid. This heat-treated product of flake magnesium hydroxide is in a high-energy metastable state and has abundant dangling bonds and lattice relaxation regions on its surface. It has extremely high chemical affinity for SiO2 and Al2O3 in the insulator ceramic matrix raw materials and potassium barium liquid phase in the second sintering aid. During the sintering process, it can form a continuous low-viscosity liquid phase earlier (about 50-100°C lower), which significantly reduces the sintering temperature and widens the sintering window. At the same time, it forms a liquid phase distribution in a specific direction to inhibit grain coarsening, promote the improvement of corundum crystallinity, optimize the microstructure, and thus improve dielectric loss, flashover resistance, and mechanical toughness.

[0041] The preparation method of this application is fully compatible with the large-scale production line of traditional high-voltage insulator ceramics, requiring no additional equipment and possessing excellent prospects for industrial production.

[0042] The high-voltage insulator ceramic of this application can significantly reduce energy consumption while maintaining excellent electrical insulation performance and mechanical strength. Attached Figure Description

[0043] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0044] Figure 1 This is a process flow diagram of the preparation process of high-voltage insulator ceramics according to one embodiment of this application.

[0045] Figure 2 XRD patterns of flake magnesium hydroxide and its heat-treated products used in the embodiments of this application.

[0046] Figure 3 The image shows an SEM image of the flake magnesium hydroxide used in the embodiments of this application, with a scale bar of 2 μm.

[0047] Figure 4 SEM images of the heat-treated products of flake magnesium hydroxide used in the embodiments of this application, (a) scale bar is 2 μm, (b) scale bar is 1 μm.

[0048] Figure 5 SEM images of the cross sections of the high-voltage insulator ceramics of Comparative Example 1 and Examples 1-3 of this application; (a) Comparative Example 1, (b) Example 1, (c) Example 2, (d) Example 3, (e) Comparative Example 2, (f) Comparative Example 3.

[0049] Figure 6 This is a comparison diagram of the density of the high-voltage insulator ceramics of Comparative Example 1 and Examples 1-3 of this application.

[0050] Figure 7 This is a comparison chart of the moisture absorption rates of high-voltage insulator ceramics in Comparative Example 1 and Examples 1-3 of this application. Detailed Implementation

[0051] The present application is further described below with reference to embodiments and examples. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Furthermore, it should be understood that after reading the teachings of this application, those skilled in the art can make various alterations or modifications to this application, and these equivalent forms also fall within the protection scope of the appended claims.

[0052] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.

[0053] The term "and / or" as used herein includes any one of two or more related listed items, as well as any and all combinations of the related listed items. These arbitrary and all combinations encompass any two related listed items, any more related listed items, or a combination of all related listed items. It should be noted that when at least three items are connected using at least two conjunctions selected from "and / or," it should be understood that, in this application, the technical solution undoubtedly includes solutions connected using "logical AND," and also undoubtedly includes solutions connected using "logical OR." For example, "A and / or B" includes three parallel solutions: A, B, and A+B. For example, the technical solution of "A, AND / OR, B, AND / OR, C, AND / OR, D" includes any one of A, B, C, and D (that is, a technical solution that is connected by "logical OR"), as well as any and all combinations of A, B, C, and D, that is, combinations of any two or three of A, B, C, and D, and also combinations of all four of A, B, C, and D (that is, a technical solution that is connected by "logical AND").

[0054] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0055] In this application, numerical intervals (i.e., numerical ranges) are involved. Unless otherwise specified, optional numerical distributions within the aforementioned numerical intervals are considered continuous and include the two endpoints (i.e., the minimum and maximum values) of the numerical range, as well as every value between these two endpoints. Unless otherwise specified, when a numerical interval points to integers within that interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints. Furthermore, when multiple ranges are provided to describe features or characteristics, these ranges may be merged. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges to which they are included.

[0056] In this application, weight can be a well-known unit of mass in the field of insulator materials, such as μg, mg, g, or kg.

[0057] join Figure 1 One aspect of this application provides a method for preparing high-voltage insulator ceramics, comprising the following steps:

[0058] S1. Mix the insulator ceramic matrix raw material, the first sintering aid, the second sintering aid and the binder to obtain a mixture;

[0059] S2. Press the mixture into shape to obtain a raw blank;

[0060] S3. Sinter the green blank to obtain high-voltage insulator ceramic;

[0061] The first sintering aid includes the heat-treated product of flake magnesium hydroxide; the preparation method of the heat-treated product of flake magnesium hydroxide includes the following steps: heating the flake magnesium oxide at 700℃-850℃ for 1h-2h;

[0062] The second sintering aid includes one or more of talc, barium carbonate, potassium carbonate, barium oxide, and potassium oxide.

[0063] The preparation method of this application uses the heat-treated product of flake magnesium hydroxide as the first sintering aid. The heat-treated product of flake magnesium hydroxide is an active sheet with a specific structure obtained by heating flake magnesium oxide at 700℃-850℃ for 1-2 hours. The main component is magnesium oxide. After mixing it with the raw material of the insulator ceramic matrix, it can induce the arrangement and orientation of the raw material of the matrix during the pressing process to obtain a dense preform. Subsequently, during the segmented heating and sintering process of the preform, the first sintering aid, together with the second sintering aid, enables the raw material of the insulator ceramic matrix to react at a relatively low temperature to generate a low eutectic glass phase. The two-dimensional flake morphology is easy to overlap to form a continuous liquid phase network, which is more conducive to mass transfer and particle rearrangement than the point contact of powder. Pinning along the grain boundary inhibits grain coarsening, achieves low-temperature densification, and constructs a textured structure with highly regular grains, dense grain boundaries and few defects. It eliminates local electric field concentration and significantly improves the brittleness of ceramics. The high-voltage insulator ceramic prepared in this way has excellent electrical insulation performance and mechanical strength. Furthermore, this preparation method is fully compatible with the large-scale production line of traditional high-voltage insulator ceramics, requiring no additional equipment and possessing excellent prospects for industrial production.

[0064] In some embodiments, the thickness of the heat-treated flake magnesium hydroxide product is 0.1 μm-0.2 μm. Exemplarily, the thickness of the heat-treated flake magnesium hydroxide product can be, but is not limited to, 0.1 μm, 0.13 μm, 0.16 μm, 0.19 μm, and 0.2 μm. Within the above thickness range, the heat-treated flake magnesium hydroxide product maintains a high aspect ratio and specific surface area, which is beneficial for its directional distribution and reaction with the raw materials.

[0065] In some embodiments, the aspect ratio of the heat-treated flake magnesium hydroxide product is (2-10):1. Exemplarily, the aspect ratio of the heat-treated flake magnesium hydroxide product can be, but is not limited to, 2:1, 4:1, 6:1, 8:1, or 10:1. Within the above aspect ratio range, a higher aspect ratio allows the heat-treated flake magnesium hydroxide product to undergo a certain orientation during the pressure of compression molding, causing the heat-treated flake magnesium oxide to align in a specific direction. This facilitates the subsequent formation of a liquid phase region in that specific direction, improving ceramic properties.

[0066] In some implementations, the ceramic matrix material for the insulator includes quartz and alumina.

[0067] In some embodiments, the insulator ceramic material comprises 60-65 parts of quartz and 37-47 parts of alumina by weight. Exemplarily, the weight percentages of quartz may be, but are not limited to, 60, 61, 62, 63, 64, or 65 parts; and the weight percentages of alumina may be, but are not limited to, 37, 39, 41, 43, or 47 parts.

[0068] In some embodiments, the particle size D50 of the alumina powder is 200 nm to 400 nm. For example, the particle size D50 of the alumina powder can be, but is not limited to, 200 nm, 250 nm, 300 nm, 350 nm, or 400 nm.

[0069] In some embodiments, the binder includes one or more of polyvinyl alcohol and polyvinyl butyral. The polymers exemplified above have a molecular weight in the range of 10,000-200,000 and have the function of increasing adhesion and enhancing the strength of the preform.

[0070] In some embodiments, the mass ratio of the insulator ceramic matrix raw material to the first sintering aid is 100:(1-4). Exemplarily, the mass ratio of the insulator ceramic matrix raw material to the first sintering aid can be 100:1, 100:2, 100:3, 100:4, etc. Within the above-mentioned addition range, heat-treated flake magnesium oxide can provide sufficient directional liquid phase while avoiding agglomeration due to excessive addition, thus achieving synergistic maintenance of electrical insulation performance and mechanical strength at low sintering temperatures.

[0071] In some embodiments, the mass ratio of the insulator ceramic matrix material to the binder is 100:(0.5-0.8). For example, the mass ratio of the insulator ceramic matrix material to the binder can be 100:0.5, 100:0.6, 100:0.7, 100:0.8, etc.

[0072] In some embodiments, the mass ratio of the insulator ceramic matrix raw material to the second sintering aid is 100:(7-9). Exemplarily, the mass ratio of the insulator ceramic matrix raw material to the second sintering aid can be 100:7, 100:7.5, 100:8, 100:8.5, 100:9, etc.

[0073] In some embodiments, the step of mixing the insulator ceramic matrix material, the first sintering aid, the second sintering aid, and the binder includes:

[0074] The insulator ceramic matrix raw material and the first sintering aid are mixed and ball-milled to obtain the first mixture; the ball milling conditions include: the ball milling speed is 100rpm-200rpm and the ball milling time is 6h-8h.

[0075] The first mixture, the second sintering aid, and the binder are mixed.

[0076] In some embodiments, the ball milling speed is 100 rpm-200 rpm, and the ball milling time is 6 h-8 h; further, the ball milling speed is 100 rpm-150 rpm. Exemplarily, the ball milling speed can be, but is not limited to, 100 rpm, 120 rpm, 130 rpm, 140 rpm, or 150 rpm; the ball milling time can be, but is not limited to, 6 h, 6.5 h, 7 h, 7.5 h, or 8 h.

[0077] In some embodiments, the conditions for ball milling also include: ball milling using mixed grinding balls;

[0078] The mixed grinding balls include a first grinding ball, a second grinding ball, and a third grinding ball with a mass ratio of 1:(0.8-1.2):(0.8-1.2);

[0079] The first grinding ball has a particle size of 4.5mm-5.5mm;

[0080] The second grinding ball has a particle size of 7.5mm-8.5mm;

[0081] The particle size of the third grinding ball is 9.5mm-10.5mm.

[0082] In some embodiments, the first, second, and third grinding balls are made of zirconium oxide.

[0083] In some embodiments, the step of molding the mixture includes: loading the mixture into a mold and pressing it at 10 MPa to 15 MPa. Exemplarily, the pressing pressure can be, but is not limited to, 10 MPa, 11 MPa, 12 MPa, 13 MPa, 14 MPa, or 15 MPa.

[0084] In some implementations, the pressure applied during the compression molding process is a directional pressure.

[0085] In some implementations, the sintering process includes:

[0086] The temperature was increased from 20℃-40℃ to 650℃-750℃ at a rate of 4.5℃ / min-5.5℃ / min.

[0087] The temperature was increased from 650℃-750℃ to 1275℃-1325℃ at a rate of 2.5℃ / min-3.5℃ / min.

[0088] Keep warm at 1275℃-1325℃ for 25-35 minutes;

[0089] The temperature was reduced from 1275℃-1325℃ to 1225℃-1250℃ at a rate of 0.5℃ / min-1.5℃ / min.

[0090] Keep warm at 1225℃-1250℃ for 2-3 hours.

[0091] One or more embodiments of this application also provide high-voltage insulator ceramics, which are prepared using the preparation method described above.

[0092] In some embodiments, the high-voltage insulator ceramic has one or more of the following characteristics:

[0093] (1) Breakdown strength ≥ 10 kV / mm;

[0094] (2) Bending strength ≥ 100 MPa.

[0095] The following are some specific examples.

[0096] For experimental parameters not specified in the following specific embodiments, please refer to the guidelines given in this application, or consult experimental manuals or other experimental methods known in the art, or refer to the manufacturer's recommended experimental conditions. Raw materials and reagents not mentioned can be obtained commercially, or can be prepared by those skilled in the art using known methods.

[0097] Example 1

[0098] This embodiment provides a method for preparing the high-voltage insulator ceramic of this application, including the following steps:

[0099] (1) Calcine the flake magnesium hydroxide at 800℃ for 1.5h, and then cool it down naturally after calcination to obtain the heat-treated product of flake magnesium hydroxide.

[0100] (2) Weigh the following substances in parts by mass: 60 parts of quartz, 40 parts of alumina powder, 2 parts of heat-treated flake magnesium hydroxide (first sintering aid), 0.7 parts of polyvinyl alcohol (binder) with a degree of polymerization of 1000, and 7.5 parts of barium carbonate-potassium carbonate mixed powder (the mass ratio of barium carbonate to potassium carbonate is 1:1, second sintering aid).

[0101] (3) The heat-treated products of quartz, alumina powder and flake magnesium hydroxide are mixed and ball-milled at 150 rpm for 7 hours. The grinding balls are zirconia balls (the first grinding ball, the second grinding ball and the third grinding ball are in a 1:1:1 ratio; the particle size of the first grinding ball is 5 mm; the particle size of the second grinding ball is 8 mm; the particle size of the third grinding ball is 10 mm) to obtain the first mixture.

[0102] (4) Mix the first mixture, binder and second sintering aid to obtain a mixture.

[0103] (5) The mixture is molded under a directional pressure of 10 MPa to obtain a blank.

[0104] (6) The green blank is sintered by segmented heating. The segmented heating sintering procedure is as follows: heating from room temperature (about 25°C) to 700°C at a rate of 5°C / min; heating from 700°C to 1300°C at a rate of 3°C / min; holding at 1300°C for 30 min; cooling from 1300°C to 1250°C at a rate of 1°C / min; holding at 1250°C for 3 h.

[0105] Example 2

[0106] This embodiment provides a method for preparing the high-voltage insulator ceramic of this application, which is basically the same as the preparation steps of Embodiment 1, except that: in step (2), 3 parts by mass of the heat-treated product of flake magnesium hydroxide are weighed; in step (3), the heat-treated product of quartz, alumina powder and flake magnesium hydroxide are mixed and ball-milled at 150 rpm for 6 hours; in step (6), the segmented heating and sintering procedure is as follows: heating from room temperature (about 25°C) to 700°C at a rate of 5°C / min; heating from 700°C to 1275°C at a rate of 3°C / min; holding at 1275°C for 30 minutes; cooling from 1275°C to 1250°C at a rate of 1°C / min; and holding at 1250°C for 3 hours.

[0107] Example 3

[0108] This embodiment provides a method for preparing the high-voltage insulator ceramic of this application, which is basically the same as the preparation steps of Embodiment 1, except that: in step (2), 4 parts by mass of the heat-treated product of flake magnesium hydroxide are weighed; in step (3), the heat-treated product of quartz, alumina powder and flake magnesium hydroxide are mixed and ball-milled at 150 rpm for 8 hours; in step (6), the segmented heating and sintering procedure is as follows: heating from room temperature (about 25°C) to 700°C at a rate of 5°C / min; heating from 700°C to 1300°C at a rate of 3°C / min; holding at 1300°C for 30 minutes; cooling from 1300°C to 1250°C at a rate of 1°C / min; and holding at 1250°C for 2.5 hours.

[0109] Comparative Example 1

[0110] This comparative example provides another method for preparing high-voltage insulator ceramics, which is basically the same as the preparation steps in Example 1, except that the first sintering aid is not used, and the mass fraction of the second sintering aid is increased accordingly. Specifically, it includes the following steps:

[0111] (1) Weigh the following substances in parts by mass: 60 parts quartz, 40 parts alumina powder, 0.7 parts polyvinyl alcohol (binder) with a degree of polymerization of 1000, and 9.5 parts barium carbonate-potassium carbonate mixed powder (the mass ratio of barium carbonate to potassium carbonate is 1:1, the second sintering aid).

[0112] (3) Mix quartz and alumina powder and ball mill at 150 rpm for 7 hours. The grinding balls are zirconia balls (the first grinding ball, the second grinding ball and the third grinding ball are in a 1:1:1 ratio; the particle size of the first grinding ball is 5 mm; the particle size of the second grinding ball is 8 mm; the particle size of the third grinding ball is 10 mm) to obtain the first mixture.

[0113] (4) Mix the first mixture, binder and second sintering aid to obtain a mixture.

[0114] (5) The mixture is molded under a directional pressure of 10 MPa to obtain a blank.

[0115] (6) The green blank is sintered by segmented heating. The segmented heating sintering procedure is as follows: heating from room temperature (about 25°C) to 700°C at a rate of 5°C / min; heating from 700°C to 1300°C at a rate of 3°C / min; holding at 1300°C for 30 min; cooling from 1300°C to 1250°C at a rate of 1°C / min; holding at 1250°C for 3 h.

[0116] Comparative Example 2

[0117] This comparative example provides another method for preparing high-voltage insulator ceramics, which is basically the same as the preparation steps in Example 1, except that: the second sintering aid is not used, and the mass part of the first sintering aid is increased accordingly. Specifically, it includes the following steps:

[0118] (1) Calcine the flake magnesium hydroxide at 800℃ for 1.5h, and then cool it down naturally after calcination to obtain the heat-treated product of flake magnesium hydroxide.

[0119] (2) Weigh the following substances in parts by mass: 60 parts quartz, 40 parts alumina powder, 9.5 parts heat-treated product of flake magnesium hydroxide (first sintering aid), and 0.7 parts polyvinyl alcohol (binder) with a degree of polymerization of 1000.

[0120] (3) The heat-treated products of quartz, alumina powder and flake magnesium hydroxide are mixed and ball-milled at 150 rpm for 7 hours. The grinding balls are zirconia balls (the first grinding ball, the second grinding ball and the third grinding ball are in a 1:1:1 ratio; the particle size of the first grinding ball is 5 mm; the particle size of the second grinding ball is 8 mm; the particle size of the third grinding ball is 10 mm) to obtain the first mixture.

[0121] (4) Mix the first mixture and the binder to obtain a mixture.

[0122] (5) The mixture is molded under a directional pressure of 10 MPa to obtain a blank.

[0123] (6) The green blank is sintered by segmented heating. The segmented heating sintering procedure is as follows: heating from room temperature (about 25°C) to 700°C at a rate of 5°C / min; heating from 700°C to 1300°C at a rate of 3°C / min; holding at 1300°C for 30 min; cooling from 1300°C to 1250°C at a rate of 1°C / min; holding at 1250°C for 3 h.

[0124] Comparative Example 3

[0125] This comparative example provides another method for preparing high-voltage insulator ceramics, which is basically the same as the preparation steps in Example 1, except that: the first sintering aid is directly untreated flake magnesium hydroxide, specifically including the following steps:

[0126] (1) Weigh the following substances in parts by mass: 60 parts of quartz, 40 parts of alumina powder, 2 parts of flake magnesium hydroxide (first sintering aid), 0.7 parts of polyvinyl alcohol with a degree of polymerization of 1000 (binder), and 7.5 parts of barium carbonate-potassium carbonate mixed powder (the mass ratio of barium carbonate to potassium carbonate is 1:1, second sintering aid).

[0127] (2) Quartz, alumina powder and flake magnesium hydroxide are mixed and ball-milled at 150 rpm for 7 hours. The grinding balls are zirconia balls (a first grinding ball, a second grinding ball and a third grinding ball in a 1:1:1 ratio; the particle size of the first grinding ball is 5 mm; the particle size of the second grinding ball is 8 mm; and the particle size of the third grinding ball is 10 mm) to obtain the first mixture.

[0128] (3) Mix the first mixture, binder and second sintering aid to obtain a mixture.

[0129] (4) The mixture is molded under a directional pressure of 10 MPa to obtain a blank.

[0130] (5) The green blank is sintered by segmented heating. The segmented heating sintering procedure is as follows: heating from room temperature (about 25°C) to 700°C at a rate of 5°C / min; heating from 700°C to 1300°C at a rate of 3°C / min; holding at 1300°C for 30 min; cooling from 1300°C to 1250°C at a rate of 1°C / min; holding at 1250°C for 3 h.

[0131] Morphological characteristics:

[0132] (1) Heat treatment products of flake magnesium hydroxide

[0133] A comparison of XRD patterns of flake magnesium hydroxide and its heat-treated product is shown in the figure below. Figure 2 , Figure 2 It can be seen that the diffraction peak positions of the flake magnesium hydroxide correspond completely with the magnesium hydroxide standard card, and the heat treatment product of the flake magnesium hydroxide corresponds completely with the magnesium oxide standard card, indicating that the composition of the heat treatment product of the flake magnesium hydroxide is basically magnesium oxide.

[0134] SEM image of flake magnesium hydroxide as shown below Figure 3 , Figure 3 As can be seen, the magnesium hydroxide powder has a hexagonal flake morphology; the SEM image of the heat-treated product of the flake magnesium hydroxide is shown below. Figure 4 , Figure 4 It can be seen that the heat-treated product of flake magnesium hydroxide can still maintain the flake morphology and uniform size distribution. Through measurement and calculation, it was found that the thickness of flake magnesium hydroxide before and after treatment is between 0.1μm and 0.2μm, and the diameter-to-thickness ratio is between 2:1 and 10:1.

[0135] (2) High-voltage insulator ceramic

[0136] Comparison of SEM images of the cross-sections of the high-voltage insulator ceramics in Examples 1-3 and Comparative Example 1 is shown below. Figure 5 , Figure 5 It is evident that the pore density and impurity content of the high-voltage insulator ceramic are significantly reduced.

[0137] Performance testing:

[0138] The high-voltage insulator ceramics prepared in the Examples and Comparative Example 1 were subjected to the following tests:

[0139] (1) Ceramic density test

[0140] The density of ceramics was tested using Archimedes' displacement method. The ceramic sheet was baked at 105℃ for 30 minutes, cooled to room temperature, and its dry weight M0 was measured. Then it was placed in deionized water and its suspended mass M in the water was measured.

[0141] Density (g / cm³) 3 =M0 / (M0-M).

[0142] (2) Ceramic moisture absorption rate test

[0143] The ceramic sheet was baked at 105℃ for 30 minutes, cooled to room temperature and weighed for its dry weight M0. Then it was placed in deionized water, vacuumed to 0.1MPa, held for 10 minutes, slowly depressurized and continued to soak for 10 minutes. The surface water was wiped off and the wet weight M was weighed.

[0144] Moisture absorption rate (%) = (M-M0) / M0×100.

[0145] (3) Breakdown strength test

[0146] The breakdown strength test was conducted in accordance with the standard GB / T1408.1-2016 "Electrical strength test method for insulating materials - Part 1: Test at power frequency".

[0147] (4) Bending strength test

[0148] The breakdown strength test was conducted in accordance with the standard GB / T 8411.2-2008 "Ceramic and Glass Insulating Materials - Part 2: Test Methods".

[0149] The test results are shown in Table 1. Figure 6 and Figure 7 .

[0150] Table 1 shows the performance test results of the high-voltage insulator ceramics in the examples and comparative examples.

[0151]

[0152] As shown in Table 1, comparing Examples 1-3 and Comparative Examples 1-3, it can be seen that the high-voltage insulator ceramics prepared in the embodiments of this application have higher crystallinity, and the breakdown strength and bending strength are significantly improved compared with traditional high-voltage insulator ceramics.

[0153] The density test results of the high-voltage insulator ceramics in Examples 1-3 and Comparative Examples 1-3 are as follows: Figure 6 , Figure 6 It is evident that the density of the high-voltage insulator ceramics in each embodiment is higher than that in Comparative Example 1.

[0154] The comparison results of the moisture absorption rate tests of the high-voltage insulator ceramics in Examples 1-3 and Comparative Examples 1-3 are as follows: Figure 7 , Figure 7 It is evident that the moisture absorption rates of each embodiment are significantly lower than those of Comparative Example 1.

[0155] The technical features of the above-described embodiments and examples can be combined in any suitable manner. For the sake of brevity, not all possible combinations of the technical features in the above-described embodiments and examples are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0156] The embodiments described above merely illustrate several implementation methods of this application and should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Furthermore, it should be understood that after reading the above teachings, those skilled in the art can make various alterations or modifications to this application, and the equivalent forms obtained also fall within the protection scope of this application. It should also be understood that technical solutions obtained by those skilled in the art based on the technical solutions provided in this application through logical analysis, reasoning, or limited experimentation are all within the protection scope of the appended claims. Therefore, the protection scope of this patent application should be determined by the appended claims, and the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing high-voltage insulator ceramics, characterized in that, Includes the following steps: The insulator ceramic matrix raw material, the first sintering aid, the second sintering aid and the binder are mixed to obtain a mixture; The mixture is pressed into shape to obtain a raw blank; The green blank is sintered to obtain the high-voltage insulator ceramic; The first sintering aid includes a heat-treated product of flake magnesium hydroxide; the preparation method of the heat-treated product of flake magnesium hydroxide includes the following steps: heating flake magnesium hydroxide at 700℃-850℃ for 1h-2h; The second sintering aid includes one or more of talc, barium carbonate, potassium carbonate, barium oxide, and potassium oxide.

2. The method for preparing high-voltage insulator ceramics according to claim 1, characterized in that, The thickness of the flake magnesium hydroxide is 0.1 μm-0.2 μm, and the aspect ratio is (2-10):1; and / or, The thickness of the heat-treated flake magnesium hydroxide is 0.1 μm-0.2 μm, and the aspect ratio is (2-10):

1.

3. The method for preparing high-voltage insulator ceramics according to claim 1, characterized in that, The ceramic matrix materials for insulators include quartz and alumina; and / or, The adhesive includes one or more of polyvinyl alcohol and polyvinyl butyral.

4. The method for preparing high-voltage insulator ceramics according to claim 3, characterized in that, The ceramic matrix raw material for the insulator, by weight, comprises 60-65 parts of quartz and 37-47 parts of alumina; and / or, The alumina is alumina powder; the particle size D50 of the alumina powder is 200nm-400nm.

5. The preparation method according to any one of claims 1-4, characterized in that, The mass ratio of the insulator ceramic matrix raw material to the first sintering aid is 100:(1-4); and / or, The mass ratio of the insulator ceramic matrix raw material to the second sintering aid is 100:(7-9); and / or, The mass ratio of the insulator ceramic matrix raw material to the binder is 100:(0.5-0.8).

6. The preparation method according to any one of claims 1-4, characterized in that, The step of mixing the insulator ceramic matrix raw material, the first sintering aid, the second sintering aid, and the binder includes: The insulator ceramic matrix raw material and the first sintering aid are mixed and ball-milled to obtain the first mixture; the ball milling conditions include: the ball milling speed is 100rpm-200rpm and the ball milling time is 6h-8h. Mix the first mixture, the second sintering aid, and the binder; and / or, The step of molding the mixture includes: loading the mixture into a mold and pressing it at 10MPa~15MPa.

7. The preparation method according to claim 6, characterized in that, The conditions for ball milling also include: using mixed grinding balls for ball milling; The mixed grinding balls include a first grinding ball, a second grinding ball, and a third grinding ball with a mass ratio of 1:(0.8-1.2):(0.8-1.2); The first grinding ball has a particle size of 4.5mm-5.5mm; The particle size of the second grinding ball is 7.5mm-8.5mm; The particle size of the third grinding ball is 9.5mm-10.5mm.

8. The preparation method according to any one of claims 1-4, characterized in that, The sintering process includes: The temperature was increased from 20℃-40℃ to 650℃-750℃ at a rate of 4.5℃ / min-5.5℃ / min. The temperature was increased from 650℃-750℃ to 1275℃-1325℃ at a rate of 2.5℃ / min-3.5℃ / min. Keep warm at 1275℃-1325℃ for 25-35 minutes; The temperature was reduced from 1275℃-1325℃ to 1225℃-1250℃ at a rate of 0.5℃ / min-1.5℃ / min. Keep warm at 1225℃-1250℃ for 2-3 hours.

9. A high-voltage insulator ceramic, characterized in that, It is prepared by the preparation method described in any one of claims 1-8.

10. The high-voltage insulator ceramic according to claim 9, characterized in that, The high-voltage insulator ceramic has one or more of the following characteristics: (1) Breakdown strength ≥ 10 kV / mm; (2) Bending strength ≥ 100 MPa.